1.54. Rozwiąż równania: a) 2 ^ (x + 2) – 2 ^ (x – 1) = 14 d) b) 3**2 25 5 d) 5 ^ (x + 2) * 7 ^ (2x + 4) = 21 ^ (x + 1) f) 9 9 ^ (3x + 2) * 5 ^ (10x + 4) = 15 ^ (3x + 2) * 25 ^ (2x) b) 3 ^ (x + 1) – 3 ^ x – 3 ^ (x – 1) = 15 d) 7 * 4 ^ x – 2 ^ (2x + 1) = 26 + 7 * 4 ^ (x – 1) f) 5 * 2 ^ (3x) + 8 ^ x – 2 * 4 ^ (15x) = 16 (x ^ 2)/(x * x ^ 2) = x – 1 c) 8 * 5 ^ x + 7 * 5 ^ (x – 1) = 22 + 5 ^ (x + 1) e) 3 ^ (2x) + 4/27 = 2 * 3 ^ (2x + 1) – 9 ^ x

1.54. Rozwiąż równania: a) 2 ^ (x + 2) – 2 ^ (x – 1) = 14 d) b) 3**2 25 5 d) 5 ^ (x + 2) * 7 ^ (2x + 4) = 21 ^ (x + 1) f) 9 9 ^ (3x + 2) * 5 ^ (10x + 4) = 15 ^ (3x + 2) * 25 ^ (2x) b) 3 ^ (x + 1) – 3 ^ x – 3 ^ (x – 1) = 15 d) 7 * 4 ^ x – 2 ^ (2x + 1) = 26 + 7 * 4 ^ (x – 1) f) 5 * 2 ^ (3x) + 8 ^ x – 2 * 4 ^ (15x) = 16 (x ^ 2)/(x * x ^ 2) = x – 1 c) 8 * 5 ^ x + 7 * 5 ^ (x – 1) = 22 + 5 ^ (x + 1) e) 3 ^ (2x) + 4/27 = 2 * 3 ^ (2x + 1) – 9 ^ x 

Kliknij aby dołączyć do Akademii Matematyki

Dodaj komentarz